A retrospective study on anthropometrical, physical fitness, and motor coordination characteristics that influence dropout, contract status, and first-team playing time in high-level soccer players aged eight to eighteen years - Deprez, D. N.; Fransen, J.; Lenoir, M.; Philippaerts, R. M.; Vaeyens, R. (The Journal of Strength and Conditioning Research, 2015)
The goal of this article was twofold, and a 2-study approach was conducted. The first study aimed to expose the anthropometrical, physical performance, and motor coordination characteristics that influence dropout from a high-level soccer training program in players aged 8-16 years. The mixed-longitudinal sample included 388 Belgian youth soccer players who were assigned to either a "club group" or a "dropout group." In the second study, cross-sectional data of anthropometry, physical performance, and motor coordination were retrospectively explored to investigate which characteristics influence future contract status (contract vs. no contract group) and first-team playing time for 72 high-level youth soccer players (mean age = 16.2 years). Generally, club players outperformed their dropout peers for motor coordination, soccer-specific aerobic endurance, and speed. Anthropometry and estimated maturity status did not discriminate between club and dropout players. Contract players jumped further (p = 0.011) and had faster times for a 5-m sprint (p = 0.041) than no contract players. The following prediction equation explains 16.7% of the variance in future playing minutes in adolescent youth male soccer players: -2,869.3 + 14.6 × standing broad jump. Practitioners should include the evaluation of motor coordination, aerobic endurance, and speed performances to distinguish high-level soccer players further succeeding a talent development program and future dropout players, between 8 and 16 years. From the age of 16 years, measures of explosivity are supportive when selecting players into a future professional soccer career.